2019
DOI: 10.1007/s00203-019-01673-5
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of selected essential oils against Fusarium culmorum and F. graminearum and their secondary metabolites in wheat seeds

Abstract: Essential oils (EOs) are products of plant origin and include mixtures of different chemical compounds. These volatile substances have many interesting properties, including antifungal properties. Fungi may develop under field conditions on crops such as wheat or corn and are able to synthesize mycotoxins, which adversely affect livestock and human health. In the present study, selected EOs were used to inhibit the growth of Fusarium graminearum and F. culmorum and reduce the concentrations of mycotoxins in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 76 publications
(93 reference statements)
2
57
1
1
Order By: Relevance
“…Chitosan also significantly reduced the concentration of DON under both glasshouse and field conditions (≥74% reduction). The reduction in our in vitro experiments was higher (89%), albeit lower than that reported by Perczak et al [31], who obtained trichothecenes concentration reductions in the 94.51-100% range by using essential oils.…”
Section: Comparison Of Treatment Efficacycontrasting
confidence: 75%
See 1 more Smart Citation
“…Chitosan also significantly reduced the concentration of DON under both glasshouse and field conditions (≥74% reduction). The reduction in our in vitro experiments was higher (89%), albeit lower than that reported by Perczak et al [31], who obtained trichothecenes concentration reductions in the 94.51-100% range by using essential oils.…”
Section: Comparison Of Treatment Efficacycontrasting
confidence: 75%
“…The effect of the conjugate complex with the best performance on the growth of Fusarium fungi on wheat grain was investigated using the method described by Perczak et al [31]. 5 mL of the COS-tyrosine solution at a concentration of 1500 µg•mL −1 was mixed with 25 g of sterile spelt grain in an Erlenmeyer flask.…”
Section: Effect Of Conjugate Complexes On Mycotoxin Production and Mymentioning
confidence: 99%
“…Consumer demand for less processed foods, together with the increased concern about the use of synthetic preservatives, have directed the interest of the food industry towards natural sources of preservatives. Essential oils have been used in vitro for their antimicrobial and antioxidant properties in different fungi and bacterial species, aiming to use them as a promising technology in order to increase the shelf life of foods [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that oil extracted with n-hexane at a concentration of 3% from Pinus halepensis showed an FMGI value of 80% against the growth of B. oryzae, while the EO from Schinus terebinthifolius observed the values of 74.44% and 71.66% at 3% and 2%, respectively [35]. Moreover, Cymbopogon martinii, O. vulgare and Cinnamomum zeylanicum EOs showed significant antifungal activities against F. graminearum and F. culmorum in wheat grains with FMGI percentages of 90.99% and 68.13%, respectively [61]. The methanol extract of O. majorana showed antifungal activity against some plant pathogenic fungi including F. solani, Aspergillus niger and A. parasiticus [62].…”
Section: Molecular Identification Through the Internal Transcribed Spmentioning
confidence: 99%